Epidemiological landscape of esophageal cancer in Asia: Results from GLOBOCAN 2020. Issue 11 (14th March 2023) - Zhu, Hongcheng; Wang, Zezhou; Deng, Bingbin; Mo, Miao; Wang, Honggang; Chen, Ke; Wu, Haoxuan; Ye, Ting; Wang, Boyan; Ai, Dashan; Hao, Shennan; Tseng, Ihsuan; et al.
Abstract: Background: Esophageal cancer (EC) is a global health problem. Asia represents a huge burden of EC globally, and incidence and mortality vary considerably across different Asian regions. Methods: Data on incidence, mortality, and preference were extracted from GLOBOCAN 2020. Age‐standardized incidence and mortality rates were calculated overall by sex, age, country, region, and continent. The predicted burden of incidence and mortality in 2040 was calculated based on global demographic projections. Results: It was estimated there were 481 552 new cases of and 434 363 deaths from EC in Asia in 2020, accounting for 79.7% and 79.8% of world EC cases and deaths, respectively. EC incidence and mortality in Asia ranked the highest among all continents. Eastern Asia represents the highest age‐standardized world incidence rate (ASWIR) of 12.3 per 100 000 for all Asian regions. Western Asia represents the lowest ASWIR of 1.7 per 100 000, accounting for 0.7% of the globe. There exist obvious differences in epidemiological features in Asian countries, including incidence, mortality, prevalence, and mortality incidence ratio. There is forecast to be up to 781 000 new cases of EC in Asia by 2040, with increasing rates of 63% for incidence and 72% for mortality from 2020. Conclusions: Asia has an increasing number of EC cases and deaths. Strategies for targeting in high‐incidence areas, the elderly, and survival should be prioritized to reduce the global EC burden, especially in low‐ and middle‐income countries in Asia. Abstract : Esophageal cancer (EC) is a global health problem. EC incidence and mortality in Asia ranked the highest among all continents, and Eastern Asia represents the highest age‐standardized world incidence rate (ASWIR) of all Asian regions. Asian countries with high EC ASWIR (≥6 per 100 000) are Mongolia (17.1), Bangladesh (14.8), China (13.8), Turkmenistan (9.1), Azerbaijan (7.9), Myanmar (7.3), Japan (7.2), Pakistan (6.5), Sri Lanka (6.4), Yemen (6.4), Afghanistan (6), and Bhutan (6). China displayed the largest number of new EC cases at 324 422, accounting for 67.37% of new cases in Asia and 53.70% around the globe, followed by India (63 180 cases), Japan (26 262 cases), Bangladesh (21 745 cases), and Pakistan (10 117 cases). There exist obvious differences in epidemiological features in Asian countries, including incidence, mortality incidence ratio, and incidence by sex and age. There is forecast to be up to 781 000 new cases of EC in Asia by 2040, with increasing rates of 63% for incidence and 72% for mortality from 2020. Strategies for targeting high‐incidence areas, the elderly, and survival should be prioritized to reduce the global EC burden, especially in low‐ and middle‐income countries in Asia.